Evaluation and Ranking of Urban Drainage Systems Using SAW, TOPSIS, and VIKOR Methods: A Case Study in Bantul Regency - Arifin, Muhamad; Winarno, Setya; Kusumadewi, Sri (Research and Social Study Institute, 2025)
Background: Urban flooding and waterlogging in Bantul Regency stem from inadequate drainage systems, exacerbated by rapid urbanization, land use changes, poor infrastructure planning, and intensified rainfall due to climate change. Therefore, an integrated risk management approach compassing both structural and non-structural solutions—is crucial for improving urban drainage resilience. Conversely, the comprehensive evaluation of drainage system performance continues to pose considerable challenges. Assessments that concentrate solely on hydraulic or technical parameters while neglecting environmental, social, and economic factors—often result in suboptimal or misdirected decisions. As such, adopting a more integrative approach through multi-criteria decision-making methods, such as Multi-Attribute Decision Making (MADM), emerges as a pertinent alternative.Aims and Methods: The methods employed for MADM analysis in this study include the Simple Additive Weighting (SAW), the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), and the Vlse Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR). Each of these approaches is designed to accommodate different data characteristics, levels of analytical complexity required, degrees of uncertainty involved, computational load, and the decision maker’s experience or expertise in applying the respective method.Results: The analysis results indicate that, based on the SAW method, location A11 obtained the highest score (0.8637), signifying the poorest drainage system performance and thus requiring top-priority intervention, whereas location A77 achieved the lowest score (0.3132), indicating a well-functioning drainage condition. Using TOPSIS, location A9 ranked first with a preference value (Vi) of 0.7498, reflecting significant proximity to the ideal solution, while A6 recorded the lowest score (0.2152). Meanwhile, the VIKOR method identified location A99 as the top-ranked alternative with a VIKOR index of 16.5321, while A1 emerged as the lowest-ranked alternative with a VIKOR index of 0.0188.